Conservation of books - Bainbridge, Abigail (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Conservation of Books is the highly-anticipated reference work on global book structures and their conservation, offering the first modern, comprehensive overview on this subject. The volume takes an international approach to its subject. Written by over 70 specialists in conservation and conservation science based in 19 countries, its 26 chapters cover traditional book structures from around the world, the materials from which they are made and how they degrade, and how to preserve and conserve them. It also examines the theoretical underpinnings of conservation: what and how to treat, and the ethical, cultural, and economic implications of treatment. Technical drawings and photographs illustrate the structures and treatments examined throughout the book. Ultimately, readers gain an in-depth understanding of the materiality of books in numerous global contexts and reflect on the practical considerations involved in their analysis and treatment. Conservation of Books is a quintessential reference work for book conservators and anyone working with books, such as collection managers, librarians, curators, dealers, collectors, historians, and related professionals. It is also an indispensable text for students to complement hands-on training in this field"--
Section 1: Book Structure & History -- Section 2: Bookbinding Materials and their Degradation -- Section 3: Approaches to Conservation -- Section 4: Preventive Conservation -- Section 5: Techniques of Conservation
OCLC-licensed vendor bibliographic record.
Keywords: Books -- Conservation and restoration; ANTIQUES & COLLECTIBLES / Books; CRAFTS & HOBBIES / Bookbinding